Characterization of a Jesus Pantocrator Wooden Icon from Eighteen Century by Differential Scanning Calorimetry and Infrared and X-ray Fluorescence Spectroscopies. (2nd January 2019) - Bratu, I.; Nemeş, O. F.; Mãruţoiu, V. C.; Kácso, I.; Gh. Vlasin, D.
Abstract: The Imperial icon of Jesus Christ portrays Him as prophet and teacher, blessing with his right hand, and holding the Holy Scriptures in His left hand. The representation of the Savior, just like in the case of the Holy Mother, Mary, in the iconographic repertoire of the Imperial (Holy) icons, is depicted in the most personal and unique way, due to the importance of these icons for the church. The icon was investigated by several analytical methods both for the wooden support and for the painting materials. Fourier transform infrared spectroscopy and differential scanning calorimetry were employed for studying the nature and conservation state of the wooden support. The wooden species of the icon base was determined to be fir and fungal attack of this wood was evidenced by Fourier transform infrared spectroscopy and differential scanning calorimetry. Fourier transform infrared spectroscopy and x-ray fluorescence spectroscopy were used for the investigation of the painted materials. Gypsum was used as ground and the following paint materials were used: red by lead and red iron; green by Scheele green; blue by Vivianite; and white by gypsum and lead white. A protein binder was employed. The icon is considered to be manufactured after 1704.